Image and video compression : fundamentals, techniques, and applications /: fundamentals, techniques, and applications. (2014) - Joshi, Madhuri A; Raval, Mehul S; Dandawate, Yogesh H; Joshi, Kalyani R; Metkar, Shilpa P
No abstract available